RESULTS TESTING TECHNIQUE OF VERTICAL CLUSTERING RELATIONAL DATABASE - Mikhail V. Grankov; Alexander I. Zhukov (Advanced Engineering Research)
The results testing technique of the structural optimization of the relational databases founded on the effect leveling of the cache-system is considered. Its feasibility through the paths with object flat sharing is proved.